2016
DOI: 10.3747/pdi.2013.00274
|View full text |Cite
|
Sign up to set email alerts
|

Higher Dialysate Matrix Metalloproteinase-2 Levels are Associated with Peritoneal Membrane Dysfunction

Abstract: ♦ Background: Peritoneal dialysis (PD) patients develop progressive and cumulative peritoneal injury with longer time spent on PD. The present study aimed to a) describe the trend of peritoneal injury biomarkers, matrix metalloproteinase-2 (MMP-2) and tissue inhibitor of metalloproteinase-1 (TIMP-1), in incident PD patients, b) to explore the capacity of dialysate MMP-2 to predict peritoneal solute transport rate (PSTR) and peritonitis, and c) to evaluate the influence of neutral pH, low glucose degradation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
(44 reference statements)
2
5
0
Order By: Relevance
“…10 Other researchers reported that MMP-2, plasminogen activator inhibitor 1 and CCL18 levels were associated with peritoneal membrane function, but did not report pathological data on PF. 9,36,37 In the present study, ROC analysis indicated that eDcR2-AR detected PF with a high sensitivity and specificity, suggesting that eDcR2-AR could be an effective biomarker for assessing PF in PD patients.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…10 Other researchers reported that MMP-2, plasminogen activator inhibitor 1 and CCL18 levels were associated with peritoneal membrane function, but did not report pathological data on PF. 9,36,37 In the present study, ROC analysis indicated that eDcR2-AR detected PF with a high sensitivity and specificity, suggesting that eDcR2-AR could be an effective biomarker for assessing PF in PD patients.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, peritoneal damage is associated with high expression of matrix metalloproteinase-2 (MMP-2), connective tissue growth factor (CTGF) and pentraxin 3, but these markers are not specific for peritoneal injury, especially PF. [9][10][11] Decoy receptor 2 (DcR2) is a transmembrane receptor of tumour necrosis factor-related apoptosis-inducing ligand that belongs to the tumour necrosis factor receptor superfamily. 12 DcR2 has high expression in tumours and is associated with resistance to apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous PD can cause a decrease or loss of mesothelial cells and lead to chronic peritoneal injury such as interstitial fibrosis. An Australian survey showed that MMP-2 and TIMP-1 increased linearly with the extension of PD duration, and PD duration was an independent and significant factor of MMP-2 and TIMP-1 [17]. A single-center cohort study of 86 patients with PD showed that the highest quartile of MMP-2 and of plasminogen activator inhibitor type 1 was associated with the longest duration of PD.…”
Section: Duration Of Pdmentioning
confidence: 99%
“…A meta-analysis of risk factors of EPS showed that the course of peritonitis was a risk factor affecting the development of EPS [22]. Cho et al [17] suggested that higher MMP-2 levels significantly and independently predicted future episodes of peritonitis, and there was a significant association between higher average levels of MMP-2 and a shorter time to the first onset of peritonitis.…”
Section: Peritonitismentioning
confidence: 99%